2021
DOI: 10.3389/fcell.2021.811297
|View full text |Cite
|
Sign up to set email alerts
|

Protein Tyrosine Phosphatases in Neuroblastoma: Emerging Roles as Biomarkers and Therapeutic Targets

Abstract: Neuroblastoma is a type of cancer intimately related with early development and differentiation of neuroendocrine cells, and constitutes one of the pediatric cancers with higher incidence and mortality. Protein tyrosine phosphatases (PTPs) are key regulators of cell growth and differentiation by their direct effect on tyrosine dephosphorylation of specific protein substrates, exerting major functions in the modulation of intracellular signaling during neuron development in response to external cues driving cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 205 publications
(220 reference statements)
0
6
0
Order By: Relevance
“…Recent studies have shown numerous molecular biomarkers in cancer (35)(36)(37). For example, KNG1 and FGG have been found to be correlated with the progression and prognosis of hepatocellular carcinoma (38,39), and SPP1 and CAV1 with overall survival in lung adenocarcinoma (40,41).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown numerous molecular biomarkers in cancer (35)(36)(37). For example, KNG1 and FGG have been found to be correlated with the progression and prognosis of hepatocellular carcinoma (38,39), and SPP1 and CAV1 with overall survival in lung adenocarcinoma (40,41).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, PTPRD has been involved in regulating neuronal survival and differentiation during brain development via its effects upon cell growth and differentiation by directly dephosphorylating specific protein substrates on tyrosine residues [15]. Thus, PTPRD may act as an intracellular transducer during neu-ronal development, responding to external stimuli that drive cell proliferation, survival, and differentiation [16]. Furthermore, PTPRD appears to be involved in the regulation of cognitive functions, such as learning and memory, since PTPRD-deficient mice have impaired cognitive functions, including deficits in contextual fear memory and spatial learning [17].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, despite successfully identifying many prognostic genes, these studies heavily ignored tumor heterogeneity. NB is a type of tumor intimately related to the early development and differentiation of neuroendocrine (NE) cells ( Nunes-Xavier et al, 2021 ). The intrinsic and extrinsic features of malignant NE cells can be precisely characterized using single-cell RNA sequencing (scRNA-seq) technology, which enables gene profiling and discovery of oncogenic cellular populations and associated marker genes at single-cell resolution ( Tang et al, 2009 ; Patel et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%